2006
DOI: 10.1248/bpb.29.1685
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Pig Urinary Bladder Wall: Time and Concentration Dependent Effect of Chitosan

Abstract: Chitosan in 0.5% w/v concentration enhanced the permeability of the isolated pig urinary bladder wall by desquamation of the urothelium as ascertained in our previous study. The aim of the present work was to determine the time and concentration dependence of chitosan's effect on the permeation of a model drug into the bladder wall and to establish if the mechanism of permeation enhancement depends on the concentration of chitosan used. In the permeability studies performed by the use of diffusion cells, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 23 publications
(29 reference statements)
2
34
0
Order By: Relevance
“…No deteriorating changes were found in te cells below the superficial layer, indicating that the small amounts of chitosan that very likely remain in the bladder after exchange of this polymer with PBS do not harm the cells. These findings are in agreement with our previous studies presenting a strict concentration dependent response of urothelial cells to chitosan dispersion (Kos et al 2006). The vitality of the new superficial cells was also confirmed by the instant formation of tight junctions and quick maturation of the apical membrane within the first 10 min after exposure of the cells to the luminal side of the bladder.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No deteriorating changes were found in te cells below the superficial layer, indicating that the small amounts of chitosan that very likely remain in the bladder after exchange of this polymer with PBS do not harm the cells. These findings are in agreement with our previous studies presenting a strict concentration dependent response of urothelial cells to chitosan dispersion (Kos et al 2006). The vitality of the new superficial cells was also confirmed by the instant formation of tight junctions and quick maturation of the apical membrane within the first 10 min after exposure of the cells to the luminal side of the bladder.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we found that the biopolymer chitosan, which is widely used as a food additive because of its ability to bind lipids and prevent their absorption into the digestive system, can cause destruction of the urothelium in ex vitro experiments on pieces of pig bladder (Kos et al 2006). The declared non-toxicity of chitosan made this biopolymer a promising inducer of desquamation of urothelial cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary studies on the effects of HPGs on the urothelium have showed that HPG-C 8/10 -MePEG-NH 2 nanoparticles increase the permeability of the urinary bladder wall by causing changes to the urothelial barrier function and morphology through opening of tight junctions and exfoliation of the urothelium. These effects are similar to the effects on bladder mucosa caused by chitosan dispersions, a well-established, cationic, mucoadhesive polymer, which increased the permeability of isolated pig bladder to a model drug by causing desquamation of the urothelium (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 60%
“…[27][28][29] However, the toxicity of chitosan to normal cell due to its highly positive charge is a big concern for further clinical application. 30 Therefore, we evaluated the biocompatibility of PAMAM. As shown in the Results section, PAMAM, without any surface modification, showed significant toxicity to both normal urothelial cells and bladder cancers (Figure 3), which is consistent with the previously reported results.…”
Section: Discussionmentioning
confidence: 99%